2018
DOI: 10.5603/kp.a2017.0257
|View full text |Cite
|
Sign up to set email alerts
|

Advanced and traditional electrocardiographic risk factors in pulmonary arterial hypertension: the significance of ventricular late potentials

Abstract: Ventricular LP were present in 19% of PAH patients and were the most powerful risk factor of mortality .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…After these exclusions, 31 studies remained in the present systematic review. Of these studies, three did not report the adjusted HR data (Ho et al, 1997; Kiyono, Hayano, Watanabe, Struzik, & Yamamoto, 2008; Uznańska-Loch et al, 2018); therefore, we finally included 28 eligible studies in the meta-analysis (Ablonskyte-Dudoniene et al, 2012; Al-Zaiti et al, 2014; Anastasiou-Nana et al, 2005; Aronson, Mittleman, & Burger, 2004; Batchvarov et al, 2004; Bonaduce et al, 1999; Bošković et al, 2014; Carpeggiani et al, 2005; Cebula et al, 2012; Cygankiewicz et al, 2015; Erdogan et al, 2008; Gang et al, 2011; Guzzetti et al, 2005; Harris et al, 2014; Hayano et al, 2001; Janszky et al, 2004; Kiviniemi et al, 2007; Krüger et al, 2002; La Rovere et al, 2003; Lanza et al, 1998; Y. Liu et al, 2014; P.…”
Section: Resultsmentioning
confidence: 99%
“…After these exclusions, 31 studies remained in the present systematic review. Of these studies, three did not report the adjusted HR data (Ho et al, 1997; Kiyono, Hayano, Watanabe, Struzik, & Yamamoto, 2008; Uznańska-Loch et al, 2018); therefore, we finally included 28 eligible studies in the meta-analysis (Ablonskyte-Dudoniene et al, 2012; Al-Zaiti et al, 2014; Anastasiou-Nana et al, 2005; Aronson, Mittleman, & Burger, 2004; Batchvarov et al, 2004; Bonaduce et al, 1999; Bošković et al, 2014; Carpeggiani et al, 2005; Cebula et al, 2012; Cygankiewicz et al, 2015; Erdogan et al, 2008; Gang et al, 2011; Guzzetti et al, 2005; Harris et al, 2014; Hayano et al, 2001; Janszky et al, 2004; Kiviniemi et al, 2007; Krüger et al, 2002; La Rovere et al, 2003; Lanza et al, 1998; Y. Liu et al, 2014; P.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are in contrast to most other studies with an incidence of nsVT between 5.9% and 13% ( 13 , 32 ). Likewise, in other studies patients with nsVT mainly had group 2 PH (group 1 vs. 2, 15% vs. 48%) ( 34 ). A slightly higher prevalence than the aforementioned studies (but still clearly lower than in our study) was found recently with 16.7% of patients having nsVT in a cohort of patients with PH of all groups (group 1, 2.5%; group 3, 3.1%; group 4, 1.8%; group 5, 0%) ( 35 ).…”
Section: Discussionmentioning
confidence: 52%
“…Several methods for the inclusion of HRT in implantable cardioverter defibrillators have already been suggested ( 10 12 ). Similarly, GE Healthcare implemented HRT assessment in their Holter analysis software tools MARS and CardioDay , which both have already been used for HRT analysis ( 13 15 ).…”
Section: Introductionmentioning
confidence: 99%